Corticotropin-releasing factor in the locus coeruleus as a modulator of ventilation in rats - Incheglu, Jolene M. [UNESP]; Bicego, Kenia Cardoso [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier B.V., 2016)
The locus coeruleus (LC) is a pontine noradrenergic nucleus that acts as a central chemoreceptor to CO2/pH and has been implicated in the cognitive aspects of stress responses. This participation is in part mediated by the action of corticotropin-releasing factor (CRF), which when released in these situations increases the firing frequency of LC noradrenergic neurons. Nevertheless, the role of CRF1 receptors in the LC in breathing and temperature control is unknown. Therefore, we tested the involvement of CRF1 receptors located in the LC in room air ventilation and the ventilatory response induced by hypercapnia (7% CO2) in rats. To this end, we injected CRF-R1-selective antagonists (antalarmin-1.2 and 2.4 mmol/0.1 mu L, or CP-376395-5 nmol/0.1 mu L) into the LC of male Wistar rats. Pulmonary ventilation (V-E) and body temperature (Tb, dataloggers) were measured in air, followed by 7% CO2 in unanesthetized rats. Antalarmin (higher dose) and CP-376395 in the LC caused an increase in V-E during normocapnia and hypercapnia, due to an increase in tidal volume. There were no differences in Tb between groups under normocapnia and hypercapnia. The results suggest that CRF acting on CRF1 receptors in the LC exerts a tonic inhibitory role in ventilation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Locus coeruleus; CRF receptors; Hypercapnia; Ventilation; Chemoreception